PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP MINAT BELI SEPEDA MOTOR HONDA SCOOPY DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA KONSUMEN PT. NUSANTARA SAKTI DI KOTA SEMARANG) - Kamilia Indah; Agung Budiatmo (Universitas Diponegoro, 2019)
Purchasing decisions can be influenced by a person’s buying interest in a product offered. Nowadays companies compete to get consumer’s heart to be interested in the product. Buying interest is heavily influenced by several factors. The product must be introduced to the consumer first. Companies can use a variety of ways to introduce their product, like increase their brand image and brand awareness so the product will be recognized, sought and eventually purchased by consumers. This research is conducted to explain the influence of brand image and brand awareness on buying decisions of Honda Scoopy with buying interest as intervening variable. Type of this research is using explanatory research with data collection techniques through questionnaires and interviews. The sampling of this research amounted to 100 respondents in Semarang City. Technical analysis used instrument test, cross tabulation, simple linear regression, multiple linier regression, test t, and test F. The results showed that brand image had a significant influence on buying interest (Y1), and brand awareness (X2) had a and significant influence on buying interest (Y1). The results also show that there is a significant influence between brand image and brand awareness together with interest in buying interest. Purchasing interest (Y1) has a significant influence on purchase decision (Y2).The suggestion of this research is to amplify the concept of Honda Scoopy and for brand awareness the company should do the marketing online.